2007
DOI: 10.1007/s10620-006-9589-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Digestive Enzymes

Abstract: A primary function of the pancreas is to produce digestive enzymes that are delivered to the small intestine for the hydrolysis of complex nutrients. Much of our understanding of digestive enzymes comes from studies in animals. New technologies and the availability of the sequence of the human genome allow for a critical review of older reports and assumptions based on animal studies. This report updates our understanding of human pancreatic digestive enzymes with a focus on new insights into the biology of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
296
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(311 citation statements)
references
References 183 publications
(167 reference statements)
5
296
0
10
Order By: Relevance
“…However, the toxicity, extent of biodegradability and release of entrapped drug in vivo of polymerized liposomes need to be examined. The interactions between certain methacryloyl-based polymerizable lipids and blood components indicate potential concerns regarding biocompatibility of these lipids and their polymerized counterparts (Whitcomb & Lowe, 2007).…”
Section: Stability Against the Combined Effect Of Lipase And Bile Saltsmentioning
confidence: 99%
“…However, the toxicity, extent of biodegradability and release of entrapped drug in vivo of polymerized liposomes need to be examined. The interactions between certain methacryloyl-based polymerizable lipids and blood components indicate potential concerns regarding biocompatibility of these lipids and their polymerized counterparts (Whitcomb & Lowe, 2007).…”
Section: Stability Against the Combined Effect Of Lipase And Bile Saltsmentioning
confidence: 99%
“…These hydrolytic products regulate diverse gastric functions that are under hormonal control, such as secretion of acid and pepsinogen and rate of gastric emptying (Erickson & Sim, 1990). Subsequently, the remaining proteins and polypeptides present in the chyme are released into the small intestine, where they are exposed to a variety of proteases and peptidases (see Figure 3) synthesized and released by the pancreas (i.e., the major source of proteases in the digestive system), and by the specific peptidases of the brush border of the intestinal mucosa (Whitcomb & Lowe, 2007). The single AAs, di-, and tri-peptides resulting from the intestinal digestion are taken up by enterocytes (where small peptides of up to 3 AAs are split into AAs by cytosolic peptidases) and then are used as nutrients for the human body (Untersmayr & Jensen-Jarolim, 2008).…”
Section: Protein Digestionmentioning
confidence: 99%
“…[12][13][14] Trypsin is a serine protease known to dissociate islets into fragments and single cells. 15 It has been shown that addition of protease inhibitors, such as Pefabloc, Trasylol or Ulinastatin (UTI), during islet isolation, resulted in improved yield. [16][17][18][19][20][21][22][23] However, the effects of these protease inhibitors on endogenous proteases and enzymes essential for tissue dissociation, in particular neutral protease, have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%